Deposição de glyphosate com diferentes pontas de pulverização na dessecação de plantas de Panicum maximum - Costa, Neumarcio Villanova da; Martins, Dagoberto [UNESP]; Rodrigues, Andréia Cristina Peres; Cardoso, Leonildo Alves (Revista Brasileira de Herbicidas, 2012)
The objective of this work was to evaluate the deposition of a tracer solution constituted by glyphosate (2,160 g ha-1 ) + FD & C No . 1 (2,000 ppm) blushing with different sprayer nozzles in burndown of Panicum maximum cv. Mombaça plants, besides the losses quantification of the sprayer to the soil. A randomized complete block design was used with four replications. Each experimental unit consisted of three lines with 5m long, spiced of 1.0 m. Treatments were applied 12 months after P. maximum seeding, and 40 days before application, a cut was conducted to become the area uniform. The following sprayer nozzles were evaluated: fat flan nozzle XR 110015 VS (100 L ha-1 ) and XR 11002 VS (200 L ha-1 ), cone nozzle TX-4 VS (100 L ha-1 ) and TX-8 VK (200 L ha-1 ), air induction nozzle AI 11002 VS (200 L ha-1 ) and double flat fan nozzle TJ 60 11002 VS (200 L ha-1 ). Immediately after application, 25 tillers per replication were collected and washed separately leaves and stem of each one in 150 ml of distilled water, for later quantification of the tracer in a spectrophotometer. Obtained data were adjusted to a regression curve by Gompertz model. All treatments were effective in burndown P. maximum plants, independently of the spray nozzles or used volume used, which suggests the possibility of reducing application volume and herbicide dosage in burndown desiccation the studied specie, considering the use of systemic herbicide. However, there was difference in the quantity, as well as in the uniformity of solution distribution sprayed in the evaluated targets in relation to spray nozzles used, and consequently of used volume. The cone nozzle TX-VK 8 (200 L ha-1 ), provided less spray deposition on the soil.

Objetivou-se com este trabalho avaliar a deposição de uma solução traçante constituída de glyphosate (2.160 g ha-1 ) + corante FD&C nº1 (2.000 ppm) com diferentes pontas de pulverização na dessecação de plantas de Panicum maxicum cv. Mombaça, além da quantificação das perdas da calda de pulverização para o solo. O delineamento experimental foi o de blocos casualizados, com quatro repetições. Cada unidade experimental constituiu-se de três linhas de 5,0 m de comprimento, espaçadas de 1,0 m. A aplicação dos tratamentos foi realizada 12 meses após a semeadura do capim-colonião; 40 dias antes da aplicação foi realizada uma roçagem para uniformização da área. Foram avaliadas as pontas de pulverização de jato plano XR 110.015 VS (100 L ha-1 ) e XR 110.02 VS (200 L ha-1 ), jato cônico TX-4VS (100 L ha-1 ) e TX-8 VK (200 L ha-1 ), ponta com indução de ar AI 11002 VS (200 L ha-1 ) e jato plano duplo TJ60 11002 VS (200 L ha-1 ). Imediatamente após a aplicação, foram coletados 25 perfilhos por repetição, sendo lavados separadamente as folhas e caules de cada perfilho em 150 mL de água destilada, para posterior quantificação do traçador em espectrofotômetro. Os dados foram ajustados à curva de regressão pelo modelo de Gompertz. Todos os tratamentos foram eficientes na dessecação das plantas de P. maximum, independentemente da ponta e volume utilizado, o que evidencia a possibilidade de redução do volume de aplicação e da dosagem do herbicida na dessecação de plantas de capim-colonião, considerando-se a utilização de herbicidas sistêmicos. Ressalta-se que houve diferença na quantidade e uniformidade de distribuição da calda pulverizada nos alvos avaliados em função da ponta testada e, consequentemente, do volume utilizado. A ponta TX-8 VK (200 L ha-1 ), proporcionou menor deposição de calda no solo.
Glyphosate deposition with different aprayer nozzles in burndown of Panicum maximum plants
Keywords: Chemical control; Technology of application; Tracer and forage; Controle químico; Tecnologia de aplicação; Traçador; Forrageira